Gastric dilation and air sacculitis in Chinook salmon, Oncorhynchus tshawytscha (Walbaum); correlation of macroscopic and microscopic lesions, and relationship of the syndrome to glomerulonephritis and serum biochemistry - Lumsden, J S (Journal of fish diseases, 2010)
Macroscopic and microscopic assessment procedures were developed to evaluate the severity and enable diagnosis from histological samples, of gastric dilation and air sacculitis (GDAS) in Chinook salmon, Oncorhynchus tshawytscha. Stomachs and swim bladders were examined from young fish with experimentally induced GDAS and from larger fish with the syndrome held in commercial saltwater net-pens. Fish fed a diet previously known to induce GDAS had significantly wider stomachs with decreased prominence of longitudinal stomach folds that contained larger amounts of fluid (P < 0.001), and thinner stomach walls with greater inter-nerve distances (P < 0.001), than fish fed an alternative commercial diet not associated with the syndrome. These fish also had swim bladders that were more likely to be opaque and contain more fluid (P < 0.001). These observations correlated well with selected criteria for stomach tissue (P < 0.002) and swim bladder (P < 0.04) that could be evaluated microscopically. Four stomach measurements, primarily measurements of wall or partial wall thickness and inter-nerve distances, were suitable for discriminating between affected and non-affected fish. A stomach width ratio, that was independent of fish weight and highly correlated with macroscopic stomach measurements (P < 0.0001), was particularly useful; this ratio was derived from the distances between both the outer border of the muscularis mucosa and mesothelium of the serosal surface to the stratum compactum. Serum biochemistry parameters (osmolality, calcium and magnesium) did not differ between fish fed different diets, but serum creatinine concentration was correlated with the microscopic thickness of the muscularis externa of the stomach wall and the total stomach thickness (P < 0.001 and P < 0.003, respectively). A glomerulonephritis was also noted in these fish. The severity of the lesion was not significantly related to GDAS nor to any serum biochemistry parameter assayed however